Short-Interval Sequential CAR-T Cell Infusion May Enhance Prior CAR-T Cell Expansion to Augment Anti-Lymphoma Response in B-NHL - Meng, Yuan; Deng, Biping; Rong, Luan; Li, Chuo; Song, Weiliang; Ling, Zhuojun; Xu, Jinlong; Duan, Jiajia; Wang, Zelin; Chang, Alex H.; Feng, Xiaoming; Xiong, Xiujuan; et al. (Frontiers in Oncology, 2021)
Chimeric antigen receptor (CAR)-T cell therapy emerges as a new treatment for refractory or relapsed (r/r) B-cell non-Hodgkin lymphoma (B-NHL); however, the overall response rate (ORR) of which in the B-NHL patients is much lower compared to the patients with r/r B acute lymphoblastic leukemia (B-ALL). We previously confirmed that sequential infusions of CD20 and CD22 CAR-T cells significantly improved the prognosis of the B-NHL patients, while some advanced patients still progressed to death during these CAR-T cell treatments. In this study, we showed that timely sequential administration of the second CAR-T cells could enhance expansion of prior CAR-T cells with stronger tumor-killing capacity in vitro and in vivo. We further conducted compassionate treatments on two advanced B-NHL patients with short-interval sequential infusions of CD19/22/20 CAR-T cells. Disease progression was observed in both patients after primary CAR-T cell infusion but robust re-expansion of prior CAR-T cells and anti-tumor effects was induced by infusion of a secondary CAR-T cells. These results indicate sequential infusions of CAR-T cells with a short interval may improve therapeutic efficacy in the B-NHL patients by promoting expansion of prior CAR-T cells.